2010
DOI: 10.1099/mic.0.033399-0
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis in a hyper-invasive clinical isolate of Campylobacter jejuni reveals a number of genes with potential roles in invasion

Abstract: Transposon mutagenesis has been applied to a hyper-invasive clinical isolate of Campylobacter jejuni, 01/51. A random transposon mutant library was screened in an in vitro assay of invasion and 26 mutants with a significant reduction in invasion were identified. Given that the invasion potential of C. jejuni is relatively poor compared to other enteric pathogens, the use of a hyper-invasive strain was advantageous as it greatly facilitated the identification of mutants with reduced invasion. The location of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…However, it may be possible that Fuc ϩ strains of C. jejuni have a competitive advantage in another host species due to variation in nutrient availability (e.g., amino acids), microbiome, and structural differences of host mucin. Interestingly, transposon mutagenesis identified fucP as an invasion determinant, since transposon insertion in this gene led to reduced invasion of cultured cells (22). How fucP contributes to the invasion process is unknown, but the finding illustrates the functional diversity of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be possible that Fuc ϩ strains of C. jejuni have a competitive advantage in another host species due to variation in nutrient availability (e.g., amino acids), microbiome, and structural differences of host mucin. Interestingly, transposon mutagenesis identified fucP as an invasion determinant, since transposon insertion in this gene led to reduced invasion of cultured cells (22). How fucP contributes to the invasion process is unknown, but the finding illustrates the functional diversity of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Signature-tagged transposon mutagenesis has shown Campylobacter colonization in chickens to be complex and dynamic (Grant et al, 2005), and furthermore, screening of a transposon-based mutant library has identified C. jejuni genes that are related to polymyxin resistance and to acid adaptation of the pathogen (Lin et al, 2009;Reid et al, 2008). Additionally, transposon mutagenesis in a clinical isolate of C. jejuni has detected 26 mutants with a clearly reduced invasion capacity (Javed et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro invasion and adhesion assay. The adhesion and invasion potentials of all strains were determined using in vitro invasion and adhesion assays as described earlier (19). Briefly, Caco-2 cell monolayers were grown in two 24-well cell culture plates.…”
Section: Methodsmentioning
confidence: 99%
“…Motility assays were undertaken using Mueller-Hinton broth supplemented with 0.4% agar as described earlier (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation